An Analysis of Teachers’ Pedagogical/ Proffesional Learning a Practice Competence in Teaching English at SMP Negeri 4 Baranti - Jumrah; Andi Asrifan; Buhari; Sam Hermansyah (MultiTech Publisher, 2023)
This research uses a descriptive qualitative method as a research methodology. This research was conducted to determine Teacher Pedagogic Competence/Professional Learning Practices in English Language Learning based on the Directorate General of GTK, Ministry of Education and Culture Number 6565/B/GT/2020. The population and sample in this study were all 3 teachers at SMP Negeri 4 Baranti. Data collection methods used in this study were questionnaires and interviews.The results showed that teachers' perceptions of Teacher Pedagogic Competence/Professional Learning Practices in English Language Learning based on the Director General of GTK of the Ministry of Education and Culture Number 6565/B/GT/2020 at Baranti 4 Public Middle School received a response with the presentation results on indicators of developing a classroom environment that facilitates student learning by safe and comfortable shows results of 3 (100%) in the average category, on design indicators shows results (100%) average category, indicators assess, provide input, and send learning reports show results of 1 (33%) in the medium category , 2 (67%) in the bad category, and on indicators that involve parents/guardians and the community in learning shows results 3 (100%) in the poor category